Migration and its effects on rural development: a case study of Keta district, Ghana - Braima, Keikura Seingah (2012)
A thesis submitted to the Board of Postgraduate Studies, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfilment of the requirement for the award of the Degree of Master of Science in Development Planning and Management.